2010
DOI: 10.1186/1471-2458-10-409
|View full text |Cite
|
Sign up to set email alerts
|

Community perceptions of malaria and malaria treatment behaviour in a rural district of Ghana: implications for artemisinin combination therapy

Abstract: BackgroundArtesunate-amodiaquine (AS-AQ) was introduced in Ghana as the first line drug for treatment of uncomplicated malaria in 2004. We report the perceptions of malaria and malaria treatment behaviour, the community awareness of and perceptions about AS-AQ two years after the introduction of this ACT treatment for malaria.MethodsTwo surveys were conducted; a cross-sectional survey of 729 randomly selected household heads (urban-362, rural-367) and 282 women with children < 5 years (urban-121, rural-161) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 17 publications
(17 reference statements)
3
42
0
Order By: Relevance
“…The community chemical shops are usually the first point of seeking medical care in the community and malaria diagnosis in the shops is mainly presumptive [23]. Currently, Artesunate-amodiaquine is the first line drug for the treatment of uncomplicated malaria in Ghana.…”
Section: Methodsmentioning
confidence: 99%
“…The community chemical shops are usually the first point of seeking medical care in the community and malaria diagnosis in the shops is mainly presumptive [23]. Currently, Artesunate-amodiaquine is the first line drug for the treatment of uncomplicated malaria in Ghana.…”
Section: Methodsmentioning
confidence: 99%
“…However, Chinese travelers often take ACTs to treat malaria in Africa. Despite the fact that AS plus AQ was introduced in Ghana as the first-line drug for treatment of uncomplicated malaria in 2004 (42), no evidence has shown that antimalarial resistance has occurred due to drug abuse. Therefore, more related research should be carried out to determine whether mutation of the K13 propeller has possibly occurred in the infecting Plasmodium species or if it has appeared in the general population in the GMS.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies have suggested that urban dwellers are more likely to have greater knowledge of malaria than people who reside in rural areas because they have higher levels of literacy and greater exposure to educational media [9], [10].…”
Section: Introductionmentioning
confidence: 99%